Simulation softwares applied in inventory management: a systematic review of the literature - Almeida, Lucas da Silva; Silva, Keren Karolyne Nóbrega; Nunes, Paloma dos Santos Alves; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2024)
In such a competitive scenario, inventory management becomes a strategic tool in the differentiation process, as asset management is crucial to business success. In this sense, the use of software for modeling and simulation is presented as a facilitator in formulating hypotheses and predicting the effects arising from changes that may be made. Therefore, the present study aims to identify the most used simulation software for solving inventory problems. For this, the method used is a systematic review of the literature, in order to map and strengthen the business/academic benefits that the link between inventory management and computer simulation guaranteed in the production process. As a result, the numerous studies reinforce that the most used simulation software in the optimization of inventory environments are Arena (32.5%), FlexSim (10%), VenSim (5%), with mixed modeling (25%), involving multicriteria analysis, generic algorithms, as well as other simulation software (22.5%). Finally, the difference in this research is the elaboration of a research agenda, listing the various gaps identified to deepen studies in the area, the main one being the scarcity of works in area.
Keywords: Inventory management; Simulation software; Computational simulation